The Mystic North : Symbolist Landscape Painting in Northern Europe and North America 1890-1940 - Nasgaard, Roald; Cincinnati Art Museum, Cincinnati (Toronto : Art Gallery of Ontario, 1984)
Astrup, Nikolai ; Carmichael, Franklin ; Carr, Emily ; Dove, Arthur ; Eugen, Prince ; Halonen, Pekka ; Hammershoi, Vilhelm ; Hartley, Marsden ; Jansson, Eugène ; Munch, Edvard ; Mondrian, Piet ; Nielsen, Ejnar ; Nordström, Karl ; O'Keeffe, Georgia ; etc.
The Mystic North : Symbolist Landscape Painting in Northern Europe and North America 1890-1940, Art Gallery of Ontario, Toronto, 13 January to 11 March 1984 ; Cincinnati Art Museum, Cincia31 March to 13 May 1984
English
boek
Keywords: Noord-Europa; Noord-Amerika